ANALISIS ISI SALURAN PENCERNAAN IKAN KASAU (Lobocheilos schwanefeldi) DARI PERAIRAN SUNGAI SIAK, RIAU - Chaidir P Pulungan; Deni Efizon (Berkala Perikanan Terubuk, 2011)
A Study on the food habit aspects of the kasau fish (Lobocheilos schwanefeldi) in SiakRiver was conducted from July to October 2008. Fishes were captured using gill-net and trap net.Total sample collected were 78 fishes, comprised of 17 fishes from Palas, 34 from Tebing TinggiOkura and 27 from Perawang. The Results shown that the composition of food were consisted ofsix classes, namely Cyanophyceae, Chlorophyceae, Bacillariophyceae, Xanthophyceae, Rotiferand Cladocera, and the main food was the Cyanophyceae.Closterium (Chlorophyceae) andDactylococcopsis (Cyanophyceae) were the dominant food in the digestive tract.